Specific Identification of Listeria welshimeri and Listeria monocytogenes by PCR Assays Targeting a Gene Encoding a Fibronectin-Binding Protein - Gilot, Philippe (American Society for Microbiology, 2002)
We have cloned and sequenced a Listeria welshimeri DNA fragment homologous to the previously described fibronectin-binding protein-encoding gene (fbp) of Listeria monocytogenes (P. Gilot, Y. Jossin, and J. Content, J. Med. Microbiol., 49:887-896, 2000). This L. welshimeri DNA fragment expresses a 24.8-kDa protein that binds to human fibronectin. Based on the fbp sequences, we developed novel PCR assays for the identification of L. welshimeri and L. monocytogenes.